Pregnancy outcome in women with Gaucher disease type 1 who had unplanned pregnancies during eliglustat clinical trials. Issue 1 (18th October 2020) - Lukina, Elena; Balwani, Manisha; Belmatoug, Nadia; Watman, Nora; Hughes, Derralynn; Gaemers, Sebastiaan J. M.; Foster, Meredith C.; Lewis, Grace; Peterschmitt, M. Judith
Abstract: Gaucher disease type 1 (GD1) is an inherited lysosomal storage disorder caused by deficient enzymatic activity of acid β‐glucosidase, resulting in accumulation of its substrate glucosylceramide, leading to debilitating visceral, hematologic, and skeletal manifestations. Women with GD1 are at increased risk for complications during pregnancy, delivery, and postpartum. Treatment with enzyme replacement therapy is generally recommended before and during pregnancy to reduce risks. Eliglustat, an oral substrate‐reduction therapy, is a first‐line treatment for adults with GD1 adults who have extensive, intermediate, or poor CYP2D6‐metabolizer phenotypes (>90% of patients). We report on pregnancy outcomes among women in eliglustat trials who had unplanned pregnancies and female partners of men in the trials. In four phase 2 and 3 eliglustat trials of 393 adults with GD1, women of childbearing potential were required to use contraception, have monthly pregnancy tests, and discontinue eliglustat promptly if pregnant. In phase 2 and 3 trials, 18 women had 19 pregnancies, resulting in 14 healthy infants from 13 pregnancies (one set of twins), three elective terminations, one ectopic pregnancy, one spontaneous abortion, and one in utero death. Median estimated eliglustat exposure duration during pregnancy was 38 days. In phase 1 trials (non‐GD1 subjects), one woman had a spontaneous abortion. Partners of 16 eliglustat‐treated men with GD1 had 18 pregnancies, all resulting in healthy infants. Eliglustat is not approved during pregnancy due to limited data. Guidelines for clinicians and patients with GD that address use of eliglustat in women of childbearing potential are needed.